Our current understanding of metastasis and the potential for predicting the course of head and neck squamous cell carcinoma - D.I. Zabolotnyi; E.V. Lukach; M.B. Sambur (Journal of Ophthalmology, 2019)
This review presents recent studies on the mechanisms of malignant neoplasm metastases, particularly, in head and neck squamous cell carcinoma (HNSCC). The involvement of circulating tumor cells (CTC) and cancer stem cells (CSC), and the role of epithelial-to-mesenchymal transition (EMT) and the reverse process, mesenchymal-to-epithelial transition (MET), in the establishment of metastases were noted. The major features of the EMT program are loss of E-cadherin-dependent intercellular adhesion of epithelial cells and increase in tumor cell motility and capacity for migration to and invasion of adjacent tissues and remote organs. Identifying the humoral and cell factors of epithelial cell microenvironment which induce and regulate the capacity of these cells for malignant transformation is important not only for understanding the mechanisms of oncogenesis, but also for considering whether it is possible to use them as predictive markers or therapeutic targets, which is important for clinical practice.